Dye‐containing nonaqueous dispersions derived from methanol‐soluble polymers stabilized by block–random copolymer surfactant. Issue 14 (25th December 2016) - Ezaki, Naofumi; Watanabe, Yoshifumi; Mori, Hideharu
ABSTRACT: In this study, nonaqueous emulsion solvent evaporation was utilized to prepare nonaqueous dispersions derived from various methanol‐soluble polymers, such as polyvinylpyrrolidone (PVP), polyethylene glycol, polyvinyl acetate (PVAC), and poly(acrylic acid), using a block–random copolymer surfactant; the block–random copolymer poly(SMA)88 ‐ b ‐poly(DEAGMA15 ‐ r ‐SMA14 ), composed of stearyl methacrylate, and diethanolamine‐modified glycidyl methacrylate, was used to stabilize the nonaqueous emulsions of methanol containing the polymers and an isoparaffin solvent, Isopar M. In the cases without dye, all emulsions and dispersions obtained after the evaporation of methanol exhibited nanometer‐sized particles as well as good stability. For emulsions consisting of dye‐containing methanol phases, particle sizes and stability of the obtained dispersions were dependent on the nature of the methanol‐soluble polymers. The dispersions derived from PVP and PVAC, which possibly interact weakly with the block–random copolymer and dye, exhibited good stability and a small particle size, which can be applied for inkjet printing. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44671. Abstract :